Engendering Governance After Armed Conflict: Observations From Kosovo - Holzner, Brigitte M. (Frontiers in Sociology, 2021)
This article addresses gender-responsive governance reforms in post-conflict Kosovo from two perspectives: (1) the perspective of human rights as fundamental for state-building, and (2) the resolutions of the UN Security Council regarding Women, Peace, and Security (WPS), notably the initial UNSCR 1325. Special focus is laid on women's agency in governance matters—at the level of the state and at the level of civil society. A gender approach to three dimensions of governance—political-administrative governance, security governance, and socioeconomic governance—shows successes and problems in this post-conflict society. Special attention is given to the strategies of the women's movement in reaching gender-responsive governance. Some initiatives for new masculinities address the necessity of norm change in gender governance. The analysis of the literature and documents, supplemented by interviews, reveals the transformative potential of gender governance that solidly roots in women's rights and combines a multi-actor approach at grassroots, and at national and international levels with strong alliances and very concrete actions.